(untitled) (Global Journal of Science Frontier Research, 2015)
Foliar epidermal features of four Nigerian species of the family Clusiaceae were studied. This was with a view to exploiting their systematic and taxonomic values to aid their taxonomy. Representatives of the four species were obtained from various parts in Southern Nigeria and passed through standard treatments to make permanent anatomical slides for the study by light microscopy (LM). Micrographic evidences of distinguishing and affinity taxonomic features were recorded. Variations in stomata, epidermal and guide cells attributes were obvious and they could be used as systematic evidence to taxonomically delineate these taxa even at generic levels. Data accruing from this study could help to resolve the taxonomic problems in this family and confirm their identity.